Application of new methods of environment analysis and assessment in landscape audits – case studies of urban areas like Częstochowa, Poland - Pukowiec-Kurda, Katarzyna; Myga-Piątek, Urszula (International Conference “Environmental Engineering”, 2017)
Following the 2000 European Landscape Convention, a new act strengthening landscape protection instruments has been in force since 2015. It sets forth legal aspects of landscape shaping (Dziennik Ustaw 2015, poz. 774) and introduces landscape audits at the province level. A landscape audit consists in identification and characterization of selected landscapes, assessment of their value, selection of so-called priority landscapes and identification of threats for preservation of their value. An audit complies with GIS standards. Analyses use source materials, i.e. digital maps of physical-geographical mesoregions, current topographic maps of digital resources of cartographic databases, latest orthophotomaps and DTMs, maps of potential vegetation, geobotanic regionalization, historic-cultural regionalization and natural landscape types, documentation of historical and cultural values and related complementary resources. A special new methodology (Solon et al. 2014), developed for auditing, was tested in 2015 in an urban area (Myga iątek et al. 2015). Landscapes are characterized by determining their analytic (natural and cultural) and synthetic features, with particular focus on the stage of delimitation and identification of landscape units in urban areas. Częstochowa was selected as a case study due to its large natural (karst landscapes of the Częstochowa Upland, numerous forests, nature reserves) and cultural (Saint Mary’s Sanctuary, unique urban architecture) potential. Częstochowa is also a city of former iron ore and mineral resources exploitation, still active industry, dynamic urban sprawl within former farming areas, and dynamically growing tourism. Landscape delimitation and identification distinguished 75 landscape units basing on uniform landscape background (uniform cover and use of the land). Landscape assessment used a new assessment method for anthropogenic transformation of landscape – the indicator describing the correlation between the mean shape index (MSI) and the Shannon diversity index (SHDI) (Pukowiec urda, Sobala 2016). Particular threats and planning suggestions, useful in development of urban areas, were presented for selected priority landscapes.